Creative Research Methods in the Social Sciences : A Practical Guide - Kara, Helen (Book collections on Project MUSE., 2017)
This accessible book examines the four pillars of creative research methods: arts-based research, research using technology, mixed-method research and transformative research frameworks. It offers examples in practice and shows readers why, when, and how to use them in their research.